ADAPTATION OF FIFTY GENOTYPE GOGO RICE ON THREE ENVIRONMENTAL ULTISOL SOIL ACIDITY - Agus Subekti (Widyariset, 2011)
Adaptation genotype upland rice at three environment acidity soil of Ultisol have been done in Toho West Kalimantan. This research consist of three acidity environment: environment of pH 4.5 ( without lime), environmental of pH 5.0 ( lime with dose 1 x Al-dd), and environment of pH 5.5 ( lime with dose 1.5 x Al-dd). Each environment arranged in Randomized Block Designs (RBD) with treatment ﬁfty genotype which repeated twice. Result of research indicated that genotypes which is good to be planted at environment of pH 4.5 ( without lime) are: Gajah Mungkur, IR 53234, PR 36, IR 60080 , S-4325-D-1-2-3-1, BP 1153 C-9-60, and BP 720 C-5-Si-60. There are correlation of phenotypic and genotypic indirectional between absorption of P, panicle length, number of ﬁll grain per panicle, and 1.000 ﬁll grain weight with grain weight per clump.